Phosphorus addition alleviates the inhibition of nitrogen deposition on photosynthesis of Potentilla tanacetifolia - Hao, Jianhui; Han, Hongkun; Liu, Ying; Li, Jiahuan; Yang, Jiyun; Ren, Baihui; Bai, Long (Frontiers in Environmental Science, 2023)
Atmospheric nitrogen(N) deposition increased soil active N, and excessive N content led to the increase of the ratio of nitrogen to phosphorus (N: P), which changed plant growth from N limitation to phosphorus(P) limitation. Potentilla is not only an important native greening material, but also a common diversity component in various grasslands in China. Its population fluctuation in the process of N deposition will affect the species diversity and productivity of grassland ecosystem. Potting experiment was conducted for 2 years with Potentilla tanacetifolia, a common species in the northern warm steppe, as the material. Through the interactive treatment of different N addition (0, 10, 20, 40 kg N · ha · yr-1) and P addition (4, 6, 8 kg P · ha · yr-1) gradients, to analysis the feedback effect between leaf N and P content and net photosynthetic rate (Pn). We explored the N: P threshold of N and P limitation from the perspective of Pn. The results showed that: (1) Under low soil N concentration, P addition can promote N absorption of P.tanacetifolia, while the high soil N concentration can reduce the N: P by increasing the leaf P content to weaken the limiting effect caused by nutrient imbalance of plants. (2) In N addition environment, proper P addition increased Pn by increasing stomatal conductance (Gs), while excessive P addition decreased Gs and inhibited Pn. (3) The Pn showed a single peak normal distribution characteristic with the enhancement of the N: P of leaves, and the Pn was at a high level between 14.5-17.0. It was preliminarily believed that the threshold value of N: P in leaves of P.tanacetifolia was 14.5-17.0.